2012
DOI: 10.1073/pnas.1218783109
|View full text |Cite
|
Sign up to set email alerts
|

Use of biotinylated plasmid DNA as a surrogate for HSV DNA to identify proteins that repress or activate viral gene expression

Abstract: ICP0, a key herpes simplex virus regulatory protein, functions first in the nucleus and then in the cytoplasm. The duration of its nuclear sojourn in cells transfected with DNA and then infected is related to the quantity of transfected DNA. Furthermore, ICP0 transactivates both viral genes and genes encoded by the transfected DNA. The data support the hypothesis that ICP0 is retained in the nucleus until it completes the replacement of repressive chromatin with effector proteins that enable transcription of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 88 publications
2
4
0
Order By: Relevance
“…This marked reduced expression was confirmed by Western blot (shown in Fig. C), consistent with previous biochemical data .…”
Section: Discussionsupporting
confidence: 92%
“…This marked reduced expression was confirmed by Western blot (shown in Fig. C), consistent with previous biochemical data .…”
Section: Discussionsupporting
confidence: 92%
“…S1). Many previously reported ICP0 targets were also confirmed in these data, including viral proteins UL50 [32], UL39 [32] and RS1 (ICP4) [48,49] as well as host proteins USP7 [50], USP9X [31], PRKDC [51], DDX17 [52] and WDR11 [8]. Interestingly, eight proteins were found in all three cell lines: viral proteins UL50, UL39, RS1 and UL34, and host proteins USP7, USP9X, VIM and DBN1.…”
Section: Icp0 Interactome Analysis In Hsv-1 Infected Cellssupporting
confidence: 83%
“…Some of the experiments in this study were performed transiently in plasmid transfection. It should be noted that it was previously shown that transiently transfected plasmid DNA does form chromatin with histone proteins in cells (55,56).…”
Section: Discussionmentioning
confidence: 99%